A Magnifying Glass for Virtual Imaging of Subwavelength Resolution by Transformation Optics. Issue 30 (14th June 2018) - Sun, Fei; Guo, Shuwei; Liu, Yichao; He, Sailing
Abstract: Traditional magnifying glasses can give magnified virtual images with diffraction‐limited resolution, that is, detailed information is lost. Here, a novel magnifying glass by transformation optics, referred to as a "superresolution magnifying glass" (SMG) is designed, which can produce magnified virtual images with a predetermined magnification factor and resolve subwavelength details (i.e., light sources with subwavelength distances can be resolved). Based on theoretical calculations and reductions, a metallic plate structure to produce the reduced SMG in microwave frequencies, which gives good performance verified by both numerical simulations and experimental results, is proposed and realized. The function of SMG is to create a superresolution virtual image, unlike traditional superresolution imaging devices that create real images. The proposed SMG will create a new branch of superresolution imaging technology. Abstract : Superresolution magnifying glass, which can achieve a superresolution optical illusion, is designed by transformation optics. Traditional magnifying glasses can give magnified virtual images where the detailed subwavelength information are lost. A super‐magnifying glass can produce magnified virtual images with subwavelength details, which is different from traditional methods for superresolution imaging (often produce a real image with subwavelength details).